Zombie Talk: Culture, History, Politics - Castillo, David R.; Schmid, David; Reilly, David A.; Browning, John Edgar; SpringerLink (Online service) (New York : Palgrave Macmillan US(Imprint), 2016)
Zombie Talk offers a concise, interdisciplinary introduction and deep analytical set of theoretical approaches to help readers understand the phenomenon of zombies in contemporary and modern culture. With essays that combine Humanities and Social Science methodologies, the authors examine the zombie through an array of cultural products from different periods and geographical locations: films ranging from White Zombie (1932) to the pioneering films of George Romero, television shows like AMC's The Walking Dead, to literary offerings such as Richard Matheson's I am Legend (1954) and Seth Grahame-Smith's Pride, Prejudice and Zombies (2009), among others.
Keywords: Film genres; Media and Communication